ACTIVITY TEST OF SIAM LABU (Sechium edule (Jacq.) Swartz) LEAF EXTRACT ON REDUCTION OF DARAGE URATE ACID TARGETS OF WHITE RATS (Rattus novergicus) - Tambusai, Sofia Rahmi (JURNAL BIOSAINS, 2023)
Uric acid is a substance produced from the breakdown of purines or waste products in the body, as a result of purine catabolism aided by the enzymes cguanase and xanthine oxidase. One of the green plants  used as traditional medicine is siam labu (Sechium edule). This plant is a vegetable plant belonging to the Curcubatiacae family that grows in the highlands. The purpose of this study was to test the anti-gout activity of chayote leaves in male  rats. The method used in this study started from preparing simplisia, preparing siam labu leaf extract, inducing mice with Ca-oxanate at a dose of 250 mg/kgBW and administering siam labu leaf extract at a dose of 250 mg/kgBW, 500 mg/kgBW. and 750 mg/kgBW was administered orally with intermittent observation periods of 1 hour for 6 hours. Results obtained in rats given 750 mg/kgBW of extract showed the lowest reduction of 3.88 ± 0.3 mg/dl. One-way ANOVA results  obtained a significant value p=0.00 (p<0.05), which can be concluded that there are differences in each treatment method in experimental animals. Tukey test results can be seen at 6 hours, it can be concluded that EDLS 750 mg/kg body weight with allopurinol is not significantly different.